2011
DOI: 10.1177/1744987111422423
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction and intentions to leave of new nurses

Abstract: Turnover of newly graduated nurses is of significant concern. There are continuing reports that new graduates struggle during the transition to the work setting. The purpose of this study was to examine the effects of perceived demands, control, social support and self-efficacy on the job satisfaction and intention to leave of new nurses utilising Karasek's Job Demands-ControlSupport model. A cross-sectional mailed survey was used to gather data. The sample comprised 232 new nurses working in acute care in Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 54 publications
(76 reference statements)
3
72
2
4
Order By: Relevance
“…To be eligible for participation, nurses should be full-time worker and should have a work experience of more than 1 year, because, in nursing, new graduates have reported that it takes 12 months to feel comfortable and confident practicing in the acute care setting [9,10]. A total of 658 nurses meeting the inclusion criteria for the study were selected from the Addis Ababa Health Bureau.…”
Section: Methodsmentioning
confidence: 99%
“…To be eligible for participation, nurses should be full-time worker and should have a work experience of more than 1 year, because, in nursing, new graduates have reported that it takes 12 months to feel comfortable and confident practicing in the acute care setting [9,10]. A total of 658 nurses meeting the inclusion criteria for the study were selected from the Addis Ababa Health Bureau.…”
Section: Methodsmentioning
confidence: 99%
“…[1] Some of them experience frustration, loneliness and struggling to continue their profession, accounting for a high turnover rate. [2] A study reported that the newly graduated nurses intended to leave their current job commonly at the first three to six months of employment.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, professional competence are at the management level that will enable individuals to play roles within the institutions, generating results, recognized and legitimized by themselves and by other social actors with which their work takes place (15) . In addition to these facts, we may cite other facts found in the literature related to nursing professional, such as modelling the workforce (2) , well-being and job satisfaction (16)(17)(18) , occupational stress (2,(20)(21)(22)(23) , Burnout Syndrome (2,(16)(17)19,21) , occupational fatigue (22) and violence at work (2) . Besides these, there are other complex issues and which occur during daily work as managing other professional categories within the health area and other categories (2,24) as well as the fact that other professionals are being managed by a nurse (2) .…”
Section: Introductionmentioning
confidence: 99%